PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KEPUASAN KERJA DI MODERASI OLEH KEPEMIMPINAN TRANSFORMASIONAL - Mustika, Yunita (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
This study aims to find out how much the contribution of emotional intelligence and spiritual intelligence to employee job satisfaction is moderated by transformational leadership, especially for employees in the Aceh Tamiang District Regional Secretariat. This study uses primary data sources, namely questionnaire questionnaires and data analysis techniques used are Moderated Regression Analysis (MRA).The results obtained partially emotional intelligence with a contribution of 42.5% and spiritual intelligence with a contribution of 47.6% proved to contribute positively and significantly to employee job satisfaction, for transformational leadership proved not a moderator variable but as an independent variable due to moderate 1 and moderate 2 proved to be insignificant. This means that transformational leadership does not give effect to reduce or increase the direct relationship of emotional intelligence and spiritual intelligence to employee performance, but transformational leadership partially contributes positively and significantly to employee performance.